2023
DOI: 10.36129/jog.2022.74
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcomes in the COVID-19 Omicron wave in comparison with the Delta wave: a multicenter observational study

Abstract: Objective. The aim of the study was to compare maternal and neonatal outcomes of the COVID-19 in Omicron and Delta wave. Materials and Methods.In this prospective observational multicenter study, we included unvaccinated patients who were hospitalized to deliver and who gave birth while infected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
0
9
3
Order By: Relevance
“…Even if several previous studies estimate that the Omicron variant gives less severe forms [3,4,5] and announces the end of the pandemic [11,12,13], our study showed that COVID-19 persists and the risk of severe and complicated forms caused by this variant should never be underestimated [14], especially during pregnancy [15,16,17]. This study also showed the efficiency of the RNA vaccine against the Omicron variant.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…Even if several previous studies estimate that the Omicron variant gives less severe forms [3,4,5] and announces the end of the pandemic [11,12,13], our study showed that COVID-19 persists and the risk of severe and complicated forms caused by this variant should never be underestimated [14], especially during pregnancy [15,16,17]. This study also showed the efficiency of the RNA vaccine against the Omicron variant.…”
Section: Discussioncontrasting
confidence: 42%
“…During pregnancy, the severity of COVID-19 was reduced during the Omicron wave in comparison with the Delta wave with lower rates of pneumonia requiring oxygen support [3]. In our population, maternal mortality among non-vaccinated pregnant women requiring hospital admission was reduced from 14.2% during the delta wave to 2.2%during the Omicron wave [3]. It has been reported that during pregnancy, vaccination improves maternal and perinatal outcomes by reducing the severity of COVID-19 [7].…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Since the emergence of the SARS COV2 virus in 2019 in China, many variants have been seen [1]. This may explain why COVID-19 appears with a large spectrum of clinical presentations and a nonnegligible occurrence of life-threatening and fatal complications, particularly with the Delta variant, which seems to be the most harmful [2]. COVID-19 generally manifests with fever, cough or gastro-intestinal troubles, but sometimes it can lead to severe outcomes with pneumonia or ARDS (acute respiratory distress syndrome), renal failure, thrombo-embolic events and multiple organ dysfunctions, mostly in patients with comorbidities or with immunodeficiency disorders [3].…”
Section: Introductionmentioning
confidence: 99%